Pengaruh Work Life Balance terhadap Kepuasan Kerja pada PT kaltim Diamond Coal - Nurlaili Handayani; Rinda Sandayani Karhab; Jubaidi Jubaidi (Journal Social Society, 2025)
This study aims to examine the effect of Work Life Balance on employee job satisfaction at PT Kaltim Diamond Coal. The research is based on the importance of achieving a balance between work and personal life to foster optimal job satisfaction. A quantitative approach with a simple linear regression method was employed. The sample consisted of 40 employees selected using a non-probability saturated sampling technique. Data were collected through questionnaires that had passed validity and reliability tests and analyzed using SPSS version 25. The results showed that Work Life Balance has a positive and significant effect on job satisfaction, indicated by a significance value of 0.025 (< 0.05) and a regression coefficient of 0.968. The coefficient of determination (R²) was 0.187, suggesting that 18.7% of the variation in job satisfaction is explained by Work Life Balance, while the remaining 81.3% is influenced by other factors not examined in this study. These findings highlight that improving Work Life Balance practices can serve as a strategic measure to enhance employee job satisfaction within the organization.